ON THE SPILLOVER OF EXCHANGERATE RISK INTO DEFAULT RISK - Božović, Miloš; Urošević, Branko; Živković, Boško (Economic Annals, 2009)
In order to reduce the exchange-rate risk, banks in emerging markets are typically denominating their loans in foreign currencies. However, in the event of a substantial depreciation of the local currency, the payment ability of a foreign-currency borrower may be reduced significantly, exposing the lender to additional default risk. This paper analyses how the exchange-rate risk of foreigncurrency loans spills over into default risk. We show that in an economy where foreigncurrency loans are a dominant source of financing economic activity, depreciation of the local currency establishes a negative feedback mechanism that leads to higher default probabilities, reduced credit supply, and reduced growth. This finding has some important implications that may be of special interest for regulators and market participants in emerging economies.